2015
DOI: 10.1111/cei.12462
|View full text |Cite
|
Sign up to set email alerts
|

Reduced interferon-α production by dendritic cells in type 1 diabetes does not impair immunity to influenza virus

Abstract: The increased risk and persistence of infections in diabetic condition is probably associated with defects in the cellular immune responses. We have previously shown a decrease in the production of interferon (IFN)-α by dendritic cells (DCs) in diabetic subjects. The basal level of IFN-α in splenic plasmacytoid DCs (pDCs) is also lower in non-obese diabetic (NOD) mice compared to prediabetic mice. The objective of this study was to analyse the ability of diabetic mice to mobilize innate and CD8(+) T cell-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This chronic IFN exposure over time may suppress the tonic, unstimulated response, but prime a stronger acute response, possibly via epigenetic changes [57]. This could explain why unstimulated ISG expression is high in individuals at risk for type 1 diabetes [19,26] and lower in established type 1 diabetes [58]. However, with strong acute stimulation, increased ISG expression is observed even after disease onset [59].…”
Section: Discussionmentioning
confidence: 99%
“…This chronic IFN exposure over time may suppress the tonic, unstimulated response, but prime a stronger acute response, possibly via epigenetic changes [57]. This could explain why unstimulated ISG expression is high in individuals at risk for type 1 diabetes [19,26] and lower in established type 1 diabetes [58]. However, with strong acute stimulation, increased ISG expression is observed even after disease onset [59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have reported that immunization of prediabetic NOD mice with a preparation of UV-inactivated influenza virus PR8/A/34 induced a robust titer of neutralizing anti-viral antibodies [35]. Recently, it has been shown that the influenza virus infection does not impair the antiviral immune response in NOD mice [36]. Also, human studies showed no significant difference in the titers of anti-influenza viral antibodies between nonvaccinated, genetically predisposed children to T1D and control children [37].…”
Section: Discussionmentioning
confidence: 99%
“…The humoral system, which mediates immediate defense responses by polymorphs, macrophages and dendritic antigen presenting cells to pathogens, is attenuated in diabetes mellitus 17 . Defects in adaptive immunity are associated with impaired type 1 interferon production 18 . Furthermore, increased generation of advanced glycation end-products could also inhibit the generation of interferon gamma by T lymphocytes 19 .…”
Section: Diabetes Mellitus Is Associated With Immune Dysfunction and mentioning
confidence: 99%